Systems-thinking innovations for water security - Alamanos, Angelos; Xenarios, Stefanos; Assubayeva, Aliya; Landis, Conrad Felix Michel; Dellis, Kostas; Koundouri, Phoebe (Frontiers in Water, 2025)
The concept of water security has progressed from a narrow emphasis on water supply infrastructure, primarily viewed through an engineering lens, to a comprehensive perspective encompassing technological, economic, environmental, and governance dimensions. The evolution of the water security concept, as evidenced in the relevant literature briefly reviewed in this paper, signifies a significant shift. This shift is toward a more comprehensive consideration of diverse values, stakeholders, and viewpoints by representing in an equitable manner as possible human-centric and ecosystem-based priorities. It also underscores the pressing need for transdisciplinary and more integrated approaches, as the challenges in representing the water security notion more effectively continue to mount. In response to these pressing challenges, the Global Climate Hub (GCH) initiative, operating under the UN Sustainable Development Solutions Network, employs interdisciplinary approaches comprising optimal dynamic combinations of technologies, economic analysis, and policies to devise national and regional water security strategies through inclusion approaches with relevant actors and stakeholders.